Understanding economics - Sobel, Russell S.; Gwartney, James D. (Mason, OH : South-Western Cengage Learning, 2009)
This new updated edition of UNDERSTANDING ECONOMICS, 12E INTERNATIONAL EDITION includes even more engaging elements--such as scenes from popular movies and applications of economic theory to real-world issues--to help you see how these theories apply to the world you see around you --Each chapter has been updated to reflect today's market, including analysis and explanation of measures of current economic activity. You'll also find highlights of the lives of notable economists and how they contributed to the thinking that shapes our markets today. Common economic myths are dispelled, and the "invisible hand" metaphor is applied to economic theory, demonstrating how it's working even today to stimulate the economy -- This 12th edition includes new technology features such as "John Stossel in the Classroom", where you'll watch and discuss his "20/20" segments and how they apply and reflect today's economy; a robust set of online multimedia learning tools, including video clips and free quizzes designed to support your classroom work; CengageNow, an online product giving you a personalized learning path based on your strengths and weaknesses.
THE ECONOMIC WAY OF THINKING -- The Economic Approach -- Some Tools of the Economist -- MARKETS AND GOVERNMENT -- Supply, Demand, and the Market Process -- Supply and Demand: Applications and Extensions -- Difficult Cases for the Market and the Role of Government -- The Economics of Collective Decision Making -- CORE MACROECONOMICS -- Taking the Nation's Economic Pulse -- Economic Fluctuations, Unemployment, and Inflation -- An Introduction to Basic Macroeconomic Markets -- Economic Instability -- Fiscal Policy -- Money and the Banking System -- Modern Macroeconomics: The Monetary System -- Stabilization Policy, Output, and Employment -- Creating an Environment for Growth and Prosperity -- Institutions, Policies, and Cross-Country Differences in Income and Growth -- INTERNATIONAL ECONOMICS -- Gaining from International Trade -- International Finance and the Foreign Exchange Market -- (macro split only) -- CORE MICROECONOMICS -- Consumer Demand and Elasticity -- Costs and the Supply of Goods -- Price Takers and the Competitive Process -- Price-Searcher Markets with Low Entry Barriers -- Price-Searcher Markets with High Entry Barriers -- The Supply of and Demand for Productive Resources -- Earnings, Productivity, and the Job Market -- Investment, the Capital Market, and the Wealth of Nations -- Income Inequality and Poverty -- APPLYING THE BASICS.
Includes bibliographical references and index.
1
Keywords: Economics; Core Macroeconomics; International Economics; Economic Fluctuations, Unemployment, and Inflation; Money and the Banking System; Modern Macroeconomics and Monetary Policy